Mitochondria transplant therapy improves regeneration and restoration of injured skeletal muscle. Issue 1 (5th January 2023) - Alway, Stephen E.; Paez, Hector G.; Pitzer, Christopher R.; Ferrandi, Peter J.; Khan, Mohammad Moshahid; Mohamed, Junaith S.; Carson, James A.; Deschenes, Michael R.
Abstract: Background: Injection of exogenous mitochondria has been shown to improve the ischaemia‐damaged myocardium, but the effect of mitochondrial transplant therapy (MTT) to restore skeletal muscle mass and function has not been tested following neuromuscular injury. Therefore, we tested the hypothesis that MTT would improve the restoration of muscle function after injury. Methods: BaCl2 was injected into the gastrocnemius muscle of one limb of 8–12‐week‐old C57BL/6 mice to induce damage without injury to the resident stem cells. The contralateral gastrocnemius muscle was injected with phosphate‐buffered saline (PBS) and served as the non‐injured intra‐animal control. Mitochondria were isolated from donor mice. Donor mitochondria were suspended in PBS or PBS without mitochondria (sham treatment) and injected into the tail vein of BaCl2 injured mice 24 h after the initial injury. Muscle repair was examined 7, 14 and 21 days after injury. Results: MTT did not increase systemic inflammation in mice. Muscle mass 7 days following injury was 21.9 ± 2.1% and 17.4 ± 1.9% lower ( P < 0.05) in injured as compared with non‐injured intra‐animal control muscles in phosphate‐buffered saline (PBS)‐ and MTT‐treated animals, respectively. Maximal plantar flexor muscle force was significantly lower in injured as compared with uninjured muscles of PBS‐treated (−43.4 ± 4.2%, P < 0.05) and MTT‐treated mice (−47.7 ± 7.3%, P < 0.05), but the reduction in force was not different between the experimental groups. The percentage of collagen and other non‐contractile tissue in histological muscle cross sections, was significantly greater in injured muscles of PBS‐treated mice (33.2 ± 0.2%) compared with MTT‐treated mice (26.5 ± 0.2%) 7 days after injury. Muscle wet weight and maximal muscle force from injured MTT‐treated mice had recovered to control levels by 14 days after the injury. However, muscle mass and force had not improved in PBS‐treated animals by 14 days after injury. The non‐contractile composition of the gastrocnemius muscle tissue cross sections was not different between control, repaired PBS‐treated and repaired MTT‐treated mice 14 days after injury. By 21 days following injury, PBS‐treated mice had fully restored gastrocnemius muscle mass of the injured muscle to that of the uninjured muscle, although maximal plantar flexion force was still 19.4 ± 3.7% ( P < 0.05) lower in injured/repaired gastrocnemius as compared with uninjured intra‐animal control muscles. Conclusions: Our results suggest that systemic mitochondria delivery can enhance the rate of muscle regeneration and restoration of muscle function following injury.